Taxonomia de Trichomyia Haliday in Curtis, 1839 (Diptera, Psychodidae, Trichomyiinae) na região neotropical, com ênfase nas espécies do Brasil - Araújo, Maíra Xavier (2013)
The species of the genus Trichomyia Haliday in Curtis, 1839, shows a wide morphological variation and a revision is urgently needed. Hitherto, 137 species were known for the genus, which is cosmopolitan. The Neotropical region was 68 species, most of them in Brazil. Species of Trichomyia were divided according to the number of palpus segments in two groups without taxonomic value. The subgenera currently known are Apotrichomyia Duckhouse, 1978; Dicrotrichomyia Duckhouse, 1978; Dactylotrichomyia Duchouse, 1978; Gondwanotrichomyia Duckhouse, 1980; Septemtrichomyia Bravo, 1999 and Opisthotrichomyia Bravo, 2001, being the last two exclusively Neotropical. This paper presents a revision of the subgenus Septemtrichomyia, proposes two new Neotropical subgenera: Syntrichomyia sub. nov. and Brachitrichomyia subg. nov.; and 51 new species: T. amazonensis sp. nov., T. anira sp. nov., T. aquita sp. nov., T. araguaensis sp. nov., T. atlantica sp. nov., T. bahiensis sp. nov., T. carenata sp. nov., T. bifurcata sp. nov., T. caipora sp. nov., T. cerdosa sp. nov., T. cetrae sp. nov., T. cinthiae sp. nov., T. colligate sp. nov., T. complicata sp. nov., T. conchulata sp. nov., T. confusa sp. nov., T. crinita sp. nov., T. dentata sp. nov., T. elongata sp. nov., T. grossa sp. nov., T. hileiana sp. nov., T. hispida sp. nov., T. horrida sp. nov., T. imarui sp. nov., T. incrustabilis sp. nov., T. inedita sp. nov., T. jezeki sp. nov., T. lobata sp. nov., T. longa sp. nov., T. longiseta sp. nov., T. manacapurensis sp. nov., T. mariensis sp. nov., T. mendesi sp. nov., T. mineira sp. nov., T. nortensis sp. nov., T. notata sp. nov., T. paraensis sp. nov., T. pitinguensis sp. nov., T. plumata sp. nov., T. pseudosilvatica sp. nov., T. pua sp. nov., T. puntarenas sp. nov., T. ribeiroi sp. nov., T. rondonensis sp. nov., T. sertaneja sp. nov., T. sinuosa sp. nov., T. spinicauda sp. nov., T. spinosa sp. nov., T. stangae sp. nov., T. ituberensis sp. nov., T. truncatasp. nov. Also, a redescription of T. inermis Barretto, a global list of species of Trichomyia and a key for males of the Neotropical species are presented. Presently 188 neotropical species are known, increasing in 30% the total number of known species. Certainly the Neotropical fauna is the richest between all the other faunas of the genus in the biogeographical regions of the world.